Dentistry for Jordanians with special needs. (4th December 2013) - Waldman, H. Barry; Perlman, Steven P.
ABSTRACT There are thousands of residents with disabilities in Jordan. Despite national legislation to assure individuals with disabilities needed services, including education and employment, social inclusion of these individuals is difficult since societal views exclude them from functioning as members of a community. While there are no national studies of the dental needs of individuals with disabilities in Jordan, local reports indicates limited use of dental services and the need for increased oral hygiene and restorative services. Examples of dental education accreditation standards in other countries are used as models for the improvement in the preparation of dental students to provide services for individuals with special needs.